Penguatan Budaya Subak Melalui Pemberdayaan Petani - Windia, Wayan (Jurnal Kajian Bali (Journal of Bali Studies), 2013)
Abstract The paper discusses the role and contribution of subakmember (farmers) to the culture. Generally known that thesubak system in Bali has been recognized as world heritagesince year 2012. The recognition indicating that subak isa traditional organization originally existing in Bali, andtake the important role and contribution as a buffer ofBali culture. Very important to note that the core of subakculture are harmony and togetherness. It is inline withbasic philosophy of subak, namely Tri Hita Karana (THK),the three ways to obtain happiness. The world and humanbeing certain need harmony and togetherness. There isthe contribution of subak to the world, in term of how toimplement the philosophy (Tri Hita Karana), especiallyin the daily agricultural activities. Widely known that theexistence of subak is strongly supported by farmers, as amember of subak. Farmers is a core of subak organization.Therefore is needed strong attention to the farmers life, inorder to stimulate subak sustainability.
Keywords: subak, culture, farmer, and Tri Hita Karana